2016
DOI: 10.1016/j.jor.2016.03.008
|View full text |Cite
|
Sign up to set email alerts
|

A practical way to prepare primer human chondrocyte culture

Abstract: Biological cartilage repair is one of the most important targets for orthopedic surgeons currently. For this purpose, it is mandatory to know how to prepare a chondrocyte culture. In this study, our purpose was to introduce a method enabling orthopedic surgeons to practice their knowledge and skills on molecular experimental setup at cellular level, based on our experiences from previous pilot studies. Thus, we believe it will encourage orthopedic surgeons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 28 publications
0
44
0
Order By: Relevance
“…As it is known that the sensitivity of human and animal tissues is different, therefore, the results obtained can be different and misleading as well . In many studies where animal tissues are not used, commercial cell lines are used …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As it is known that the sensitivity of human and animal tissues is different, therefore, the results obtained can be different and misleading as well . In many studies where animal tissues are not used, commercial cell lines are used …”
Section: Discussionmentioning
confidence: 99%
“…As a result, the in vitro test results, which are difficult to comply with in vivo conditions, may become even more controversial since the cell does not interact with formations such as extracellular matrix structure. Besides, since the genetic structure of the cells in the cell line has been modified, they will not carry the genotypic and/or phenotypic characteristics that they have in the human body …”
Section: Discussionmentioning
confidence: 99%
“…MTT analyses were evaluated in accordance with commercial kit bulletins on the 1st, 7th, 14th, and 21st days [1520, 24, 26]. …”
Section: Methodsmentioning
confidence: 99%
“…Recent well-proved studies have reported that half-life of growth factors is maximum 2 min. [37][38][39][40] It was emphasized that when growth factors -with protein and peptide structure -in PRP obtained from human were applied after that period, bioactivity decreased and even vanished. [37][38][39][40] When the studies in which PRP was obtained from autologous blood in clinics were considered, it was found that it was prepared from 10 to 20 min.…”
Section: -2234mentioning
confidence: 99%
“…[37][38][39][40] It was emphasized that when growth factors -with protein and peptide structure -in PRP obtained from human were applied after that period, bioactivity decreased and even vanished. [37][38][39][40] When the studies in which PRP was obtained from autologous blood in clinics were considered, it was found that it was prepared from 10 to 20 min. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Nevertheless, it takes time to apply it to cases, which makes its bioactive and effective treatment results controversy.…”
Section: -2234mentioning
confidence: 99%